Analysis of Factors Influencing Accounting Students' Interest in Public Accountant Careers (Empirical Study of Accounting Students of Universities in Surakarta City, Class 2021 and 2022) - Husna, Aufi Muaddibah; Trisnawati, Rina (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of financial rewards, perceptions of the public accounting profession, perceptions of the work environment, adversity quotient, and professional training on accounting students' interest in pursuing a career as a public accountant in accounting students at universities in Surakarta City, intakes of 2021 and 2022. This study uses primary data obtained from questionnaires with 115 respondents. The analysis methods used include descriptive statistics and multiple linear regression. The results of this study indicate that financial rewards and perceptions of the public accounting profession influence accounting students' interest in pursuing a career as a public accountant, while other variables do not have a significant influence on student interest. These findings are expected to provide insight for educational institutions, in this case, universities, regarding the factors that influence student interest in a career, especially in the public accounting profession.